In the shadow of a steel recycling plant in these neoliberal times: health disparities among Hispanics in a border colonia. Issue 5 (3rd May 2016) - Staudt, Kathleen; Dane'el, Mosi; Márquez-Velarde, Guadalupe
Abstract : Neo-liberal principles and practices of limited government and market economies prevail in many global regions, especially at borders. This research examines health outcomes in Westway colonia, immediately adjacent to a steel recycling plant owned by the largest steel corporation in the world and in the Texas–Mexico borderlands, posing the questions and testing hypotheses about the incidence of cancer and respiratory and mental illnesses in an economically and politically impoverished region of Mexican Americans and immigrants. Using community-based participatory research and drawing on sources from mixed methods – ethnographic presence and both descriptive statistics and stepwise multiple regression from a random sample of 104 households, with 400 individuals within them – we demonstrate that years living in Westway (statistically significant in multivariate analysis) and closer location (in descriptive analysis) are related to negative health outcomes. Poor mental health is related to respondents' worries about the plant, odours, noise, soot, and continuous emissions on a three-shift basis. The border location offers insights into the impact of a relatively unregulated global economy on local people in a world of considerable migration across borders. Our findings are potentially relevant in the many unequal borderlands worldwide.